Evaluation of Soft Tissue Adaptation During Retention Period - Müfide Dinçer; Belma Işık-Aslan; Nilüfer Darendeliler; Berna Ünsal-Raşit (Galenos Yayinevi, 2009)
The aim of this study was to evaluate skeletal and dental stability and the adaptation of tongue and perioral soft tissue during retention treatment period. The sample included 22 Angle class I and/or class II, skeletal class I (15 females, 7 males, mean chronologic age 17.56±1.2) cases who had 4 premolar extracted. 18 measurements on lateral cephalometric and anteroposterior films, 4 measurements on dental casts, 16 measurements of the soft tissue were carried out at the end of active orthodontic treatment (T0), at the sixth (T1) and the ninth months (T2) of retention treatment period and evaluated statistically using 'Wilcoxon test'. U6s(V) measurement showed a significant increase during T0-T1 (p<0.05) and L1s(V) measurement increased significantly during T1-T2 and T0-T2 (p<0.05). The total lingual pressures at rest and during swallowing were found significantly more than the total vestibule pressures in all retention treatment periods (T0,T1,T2) (p<0.01). Teeth positions were stable during retention although lingual pressure was more than lip and cheek pressures. Skeletal, dental measurements and soft tissue adaptation at rest were stable at the end of retention.